Changes In Starch Resistant And Glycemic Index Marinade Rice In Some Kind Of Functional - Teguh Budiharjo; Wiwik Wijaningsih; Widodo Widodo (Poltekkes Kemenkes Semarang, 2012)
This study is an experimental study using a completely randomized design with a look at the index difference glikemiks fungsioanl instant rice products. Data Analysis with SPSS 15:00 Anova for the window to test the effect of treatment on the dependent variable. Further test carried out if there is treatment effect on the dependent variable with regard to the coefficient (KK), in homogeneous conditions (less than 5% continued to use the Tukey test, 5-10% using LSD and more than 10% using Duncan. ANOVA test results indicate that some kind of marinade during pratanak the white guava leaves, green tea, onion skins and wooden cup significantly different (P less than 0.05) against the resistant starch content of rice functional. Resistant starch content increased with the amount of phenol content of marinade. There was an increase in resistant starch content when compared with rice soaked with water., The increase ranged between 25-30% of control (rice soaked with water).